(3SjQI GdEeGe jMji Hf MeRI GdYdhis
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg gPG PcQ fHPg jSjQI ef SjQI ehdGfG s
(3BNQgG (B:s
(3hUGQJ GdBf HQcI ddYHGOhecGfkG eHGQckG jbUOg GdfGS ef CWQGa GdHdGO hJdGg JQLeI dYHO Gddg Hf GdgGOi Hf CejQ GdeDefjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B12s
(3GdfSNI HgG MhGTs
(3fHPI jSQI ef jSQJg heUfaGJg hChdGOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdJGQjNs